Inoculation and co-inoculation of Bradyrhizobium japonicum and Azospirillum brasilense in soybean culture (Research, Society and Development, 2020)
Co-inoculation is a practice frequently used in Brazil because it provides positive results in soybean culture. The objective of this work was to evaluate the effect of co-inoculation and the ways of applying Bradyrhizobium japonicum and Azospirillum brasiliense on soybean culture. The experiment was carried out in the 2017/18 and 2018/19 agricultural seasons in the municipality of Chapadão do Sul - MS. The experimental design used was randomized blocks, with seven treatments: control (not inoculated and without nitrogen), Bradyrhizobium in the seed (100 mL ha-1), Bradyrhizobium in the furrow (250 mL ha-1), Bradyrhizobium in the seed + Azospirillum in the groove (100 mL ha-1 + 250 mL ha-1), Bradyrhizobium in the groove + Azospirillum in the groove (250 mL ha-1 + 250 mL ha-1); Bradyrhizobium in the seeds + Bradyrhizobium in the furrow (100 mL ha-1 +); Azospirillum in the seed + Bradyrhizobium in the furrow (100 mL ha-1 + 250 mL ha-1), with four replications. The values obtained for plant height, relative chlorophyll index and mass of one hundred grains did not exceed the control with the use of B. japonicum and A. brasilense applied to seeds or furrows, inoculated or co-inoculated, in the two studied crops. The productivity of soybeans was favored both by inoculation of B. japonicum in the seeds and by co-inoculation in furrow.